Perancangan Enterprise Architecture Pada Bidang Agroforestry Menggunakan Metode Togaf 9.1 Adm - Ega Silvana Almunadia; Tien Fabrianti Kusumasari; Iqbal Santosa (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2019)
Perum Perhutani is a State-Owned Enterprise (SOE) that focus on forest management. One of the Perum Perhutani’s main businesses is Agroforestry. To achieve the business goals of Agroforestry, Perum Perhutani requires an information system that is capable of supporting its management activities. In developing IT, Perum Perhutani has a reference, that is the SOE Regulation Number: PER-03 / MBU / 02/2018 regarding the Information Technology Management Preparation Guide that every BUMN must align business strategy with the IT strategy. So, Perum Perhutani requires the design of Enterprise Architecture. The framework that will be used in designing Enterprise Architecture is the Open Group Architecture Framework (TOGAF) and the TOGAF Architecture Development Method (ADM) method. The output of this design is a blueprint and IT Roadmap for 5 years that can be used as an implementation guide.